Books for children that cause no harm to adults/Books for adults that cause no harm to children. Orecchio Acerbo, a pioneering publishing experience in Italy - Grilli, Giorgia (Rivista di Storia dell’Educazione, 2018)
An analysis of the activity and politics of one of the most radical ground-breaking picturebook publishers in Italy prompts reflection on what publishing books for children actually means, or should mean, how to strike the fine balance between saleability and research, standardization and experimentation, how to consider children and what is ‘right’ or ‘suitable’ for them, and what is the role and responsibility of a small, independent children’s publishing house on the global scene.